Central Asia's Hidden Burden of Neglected Tropical Diseases - Hotez, Peter J.; Alibek, Ken (Public Library of Science, 2011)
The neglected tropical diseases (NTDs) are the most common infections of the world's poorest people living in developing countries [1]–[7]. They are mostly comprised of chronic parasitic and related infections, with the most common NTDs represented by the soil-transmitted helminthiases, schistosomiasis, lymphatic filariasis, onchocerciasis, and trachoma [1]. Among their common features, the NTDs result in prolonged periods of disability and actually help to promote poverty through their long-standing effects on child development and worker productivity [2]. It is not commonly appreciated that the NTDs are widespread throughout Central Asia where they are also a major determinant of poverty [8]. The five mostly landlocked Central Asian countries—Kazakhstan, Kyrgyzstan, Tajikistan, Turkmenistan, and Uzbekistan (Figure 1)—were established upon the breakup of the former Soviet Union in 1991. They are also linked in history as a vital crossroads (“the Silk Road”) between Asia and Europe and by a common geography comprised of a desert and piedmont region [9]. The five nations have a combined population of 60 million people, with three of them—Kyrgyzstan, Tajikstan, and Uzbekistan—exhibiting a Human Development Index (HDI) that is ranked below 100, whichis more or less equivalent to nations such as Guatemala, India, Indonesia, and South Africa [10].
Keywords: Research Subject Categories::MEDICINE; Central Asia; Tropical Diseases; neglected tropical diseases; NTDs